Efeito de um protocolo de exercícios baseado em realidade virtual sobre o equilíbrio postural e qualidade de vida de mulheres grávidas: ensaio clínico randomizado - Sousa, Vanessa Patricia Soares de (2016)
Introduction - Pregnancy is a period of intense hormonal, physical and emotional changes that can result in altered postural balance (PB) and worsening of quality of life (QOL). Objective - The main objective of this thesis was to investigate the influence of an exercise protocol, based on virtual reality, on PB and QOL of pregnant women. Methodology - Randomized controlled clinical trial with a sample of 57 pregnant women divided into a control group (CG = 29) and an experimental group (EG = 28). Sociodemographic, clinical and obstetric information was collected, was evaluated the PB (Balance Master System®) and Wii Fit Plus® was used to train this body function. The evaluation of the quality of life was carried out through the Quality of Life Index of Ferrans and Powers. The CG participated in 12 meetings of the Preparatory Course for Gestation, Childbirth and Postpartum (PCGCP). The GE attended the PCGCP and, simultaneously, performed the training protocol, based on RV, which consisted in the execution of 5 games for postural balance, during 12 individual sessions, held three times a week. For statistical analysis were used Student's t-tests for independent samples, Mann-Whitney, Chi-square and repeated measures ANOVA (2x2). Results - The main result of this study was that there were no intra and intergroup differences for PB (P> 0.11) and QoL (P = 0.20), indicating maintenance of these variables with the progress of pregnancy and through the implementation of the two proposed interventions. Conclusion - The results suggest that health education interventions and training with Wii Fit Plus® prevent worsening of postural balance and quality of life, expected with the onset of the pregnancy period.